Trade Policy and Structural Change - Hayato Kato; Kensuke Suzuki; Motoaki Takahashi (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We examine how tariffs affect sectoral composition and welfare in an economy with nonhomothetic preferences and sectors being complements—key drivers of structural change. Beyond their conventional role in trade protection, tariffs influence industrial structure by altering relative prices and income levels. We qualitatively characterize these mechanisms and use a quantitative dynamic model to show that a counterfactual 20-percentage-point increase in U.S. manufacturing tariffs since 2001 would have raised the manufacturing value-added share by one percentage point and increased welfare by 0.36 percent. However, if all the U.S. trading partners responded reciprocally, U.S. welfare would decline by 0.12 percent.
Keywords: F11; F13; F16; F43; O41; 330; tariff; ricardian model of trade; structural transformation; nonhomothetic preferences; capital accumulation; trade war